Health Promoting Lifestyle among Nurses of a Tertiary Level Hospital - Baral, Pramila; Tamrakar, Neeta (Journal of Karnali Academy of Health Sciences, 2020)
Background: Lifestyle-related diseases are increasing worldwide representing 63% of all deaths globally. Health-promoting behaviors among nurses may affect the quality of patient care and education. This study aims to identify the health-promoting lifestyle among nurses. Methods: Descriptive, cross-sectional study design was used among 111 nurses working in Manipal Teaching Hospital, Pokhara from November 2016 to March 2017. A simple random sampling technique (lottery method) was applied using a self-administered structured standard tool, Health Promoting Lifestyle Profile II. The analysis was done using an independent t-test. Results: The total Health-Promoting Lifestyle Profile II mean score was 137.66±19.18. The highest mean score was in spiritual growth (27.43±4.63) and lowest in physical activity (17.03±4.88). A good health-promoting lifestyle was among 60.4% of the nurses. The significant difference in the mean score of total Health-Promoting Lifestyle Profile II was found in marital status (p=0.031) and educational qualification (p=0.009). Likewise, the significant mean difference of interpersonal relations, nutrition and stress management was found with educational qualification (p < 0.05). The significant mean difference in nutrition was also found with marital status (p=0.02). There was a significant mean difference in physical activity and spiritual growth with work experience (p<0.05). Conclusion: The spiritual aspect of health has been more focused by the nurses. Along with this, nurses need to put greater emphasis on physical activity and stress management for better health.